The Development of Mathematics for Chemistry Textbook Based on Flipbook as an Alternative Learning Resources - Kharisma Purwanto, Kriesna; Resmi, Fitroh (KnE Social Sciences, 2024)
Mathematics for Chemistry course is a basic course that teaches the concept of algorithms in chemistry. Students had difficulties in learning Mathematics for Chemistry because they could not understand the reference books used. So, students need math reference books that directly refer to applications in chemistry concepts. This development research aimed to produce a textbook based on flip books that can be used as alternative learning resources in Mathematics for Chemistry courses. The development model used was the 4D Thiagarajan model with four stages: define, design, develop, and disseminate. However, in this study, the development stage was only limited to the develop stage. To collect data, we used questionnaires with experts and students as respondents. The results of Mathematics for Chemistry textbooks based on flipbook development included flipbook-based textbooks packaged in EXE. The content/material validity level was 90% (very valid), the media validity (design) level was 91.25%, the practicality level was 88% (very high), and the readability level was 89% (very high). It can be concluded that this book is suitable for use as a reference in Mathematics for Chemistry courses. For further research, it is necessary to analyze the effect of this book on improving student achievement. Keywords: mathematics, chemistry, flipbook